Cross-sectional study of gender differences in physical activity-related injuries amongst Chinese college students majoring in rehabilitation - Yu, Yanling; Li, Xian; Yan, Wangwang; Feng, Beibei; Yu, Jiadan; Wang, Yuling (Frontiers in Public Health, 2022)
The main objective of the paper was to explore the potential risk factors for physical activity-related injuries (PARI) amongst college students majoring in rehabilitation and to analyse gender differences. A random whole group sampling method was used to recruit freshmen to seniors aged 15 to 25 years from over 90 universities in China that offer rehabilitation. The total number of people included was 6032, of which 1989 were male and 4043 were female. The underlying risk factors for PARI of different genders were assessed using a structured self-management questionnaire including sociodemographic characteristics, physical activity levels, risk-taking and protective behaviours, and PARI. Totally 6032 questionnaires were obtained for final analysis, with 792 total number of injured persons (415 males, 377 females), the sum of the cumulative frequency of injuries to injured persons is 1607 (881 males, 726 females) and a PARI risk of 0.27 (males: 0.44, females: 0.18; p < 0.001) (sum of the cumulative frequency of injuries / total number of people surveyed /year). For male and female students, participation in sports teams, having a high level of PA as well as with antisocial behaviour were risk factors for developing PARI. Regarding female students, regional differences was associated with elevated odds to suffer from PARI. The prevalence rates of PARI vary between male and female students. The research subjects were university students in rehabilitation. Compared to general college students, rehabilitation students have a certain knowledge base related to injuries, which defines the specificity and research value of this subjects. This study provides guidance for reducing PARI in students in rehabilitation and may provide a basis for developing future injury prevention mechanisms for university students in general.